An Overview of Sadharanikaran Model of Communication: Future Applicability and Amendments for the Modern Era - Chowdhury, Ujjwal K. (Bodhi: An Interdisciplinary Journal, 2025)
This article aims to provide a comprehensive overview of the Sadharanikaran Model of Communication (SMC), analyze its strengths and challenges in the contemporary world, and examine its potential applications across various fields. Furthermore, it is also aimed at proposing necessary amendments to enhance its continued relevance and applicability in the evolving communication landscape of the future. Communication models serve as fundamental frameworks for understanding the complex processes involved in human interaction and meaning making. Historically, the field of communication studies has been significantly influenced by Western perspectives, with models originating from European and North American scholars often taking precedence in academic discourse. However, there is a growing recognition of the need to incorporate diverse perspectives, including those from nonWestern traditions, to achieve a more comprehensive and globally relevant understanding of communication phenomena. The development and increasing scholarly attention towards the SMC represent a significant step in this direction, challenging the traditional Eurocentric bias and underscoring the importance of indigenous knowledge systems in explaining communication.